Facial Image Denoising Using Convolutional Autoencoder Network - Tun, Naing Min; Gavrilov, Alexander I.; Tun, Nyan Linn (2020 International Conference on Industrial Engineering, Applications and Manufacturing (ICIEAM), 2020)
Noise effects can interfere the face recognition process in outdoor conditions. Therefore, image denoising topic is the classical issue in the field of image processing and computer vision subjects. In this paper, we show that the solution of denoising process using the autoencoder networks based on the ORL face database. The proposed method can support face recognition systems designed for use in an outdoor environment as the preprocessing stage and it can provide the effective results after training process.